Screening of potential probiotic Lactiplantibacillus plantarum from fermented foods and determining its hypocholesterolemic activity - Varsha S. Nangare; Dhanraj B. Nakade (The Bioscan, 2025)
A total of 80 isolates were isolated from local fermented food samples. All isolates were classified as lactic acid bacteria based on their Gram-positive, catalase-negative characteristics. The lactic acid bacterial isolates were evaluated for their ability to produce antibacterial agents against five specific pathogens. Isolates were tested for antibacterial activities. Out of 80 isolates, only 38 showed antibacterial activity. Out of 80 isolates, 38 were isolated from commercial samples, and 42 were isolated from homemade samples. Of 38 isolates from commercial samples, only 21 showed antibacterial activity against selected pathogens, while 17 did not. Among 42 isolates from homemade samples, only 17 showed antibacterial activity against the pathogens chosen, while 21 did not. Among these isolates, five isolates showed broad antibacterial activity. Among the five isolates, isolate CP2 showed the most significant cholesterol reduction (42.6%). Potential hypocholesteric isolates were identified using morphological, biochemical, and 16S rRNA identification methods. The promising isolate was identified as Lactiplantibacillus plantarum. Keywords Isolation, potential, screening, antibacterial, and cholesterol reduction